My special one. Volume 2 - Koda, Momoko (VIZ Media, 2023)
"After a mortifying rejection, Sahoko Wakaume has sworn off beautiful boys. But a chance meeting puts her in the sights of gorgeous J-pop star Kouta Kirigaya of the group Like Legend. Sahoko will need all her cynicism to defend herself against Kouta's tenderhearted and affectionate attacks to win her heart! Introverted high schooler Sahoko gathers her courage and confesses her love to the nation's top idol, Kouta Kirigaya! But he tells her he won't ever have a special someone... Not long after, Kirigaya is hit with a scandal and ends up staying with Sahoko's family!" --